2013
DOI: 10.1186/1472-6920-13-130
|View full text |Cite
|
Sign up to set email alerts
|

Empathy in Chinese medical students: psychometric characteristics and differences by gender and year of medical education

Abstract: BackgroundIn recent years in China, the tense physician-patient relationship has been an outstanding problem. Empathy is one of the fundamental factors enhancing the therapeutic effects of physician-patient relationships and is significantly associated with clinical and academic performance among students.MethodsThis cross-sectional study used the JSPE-S (The Student Version of the Jefferson Scale of Physician Empathy) to assess 902 medical students from 1st year to 4th year at China Medical University. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
132
17
15

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(198 citation statements)
references
References 23 publications
34
132
17
15
Order By: Relevance
“…As they progress in their study, they develop their study skills and exposure to different type of patients and their empathy level with them also grow. In accordance to our study, medical students in China, Korean, Kuwait and Bangladeshi [5,6,8,10] having increased level of empathy in clinical year than in basic years. This was in disagreement with what was reported about American and Iranian medical students who having increase level of empathy in basics year comparing to the clinical years.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…As they progress in their study, they develop their study skills and exposure to different type of patients and their empathy level with them also grow. In accordance to our study, medical students in China, Korean, Kuwait and Bangladeshi [5,6,8,10] having increased level of empathy in clinical year than in basic years. This was in disagreement with what was reported about American and Iranian medical students who having increase level of empathy in basics year comparing to the clinical years.…”
Section: Discussionsupporting
confidence: 57%
“…Education and Health Careat Jefferson Medical College, to measure the level of empathy among physicians and other health professionals [3].The hypothesis that empathy declines as students' progress through medical school has previously investigated in many Asian countries like Japan [4], South Korea [5], China [6], Iran [7], Bangladesh [8] and India [9], some Arabic countries as Kuwait [10], as well as other countries like UK [11], USA [12], Brazil [13] and German [14] by using the student version of Jefferson Scale of Physician Empathy (JSPE). To our knowledge, the empathy with patients among the Saudi medical students has not been studied till now.…”
Section: The Jefferson Scale Of Empathy (Jse) Was Developed At the Cementioning
confidence: 99%
“…It has been demonstrated 22 that there is gender variability in relation to empathy in a study in 18 dental schools in Latin America. As a consequence, it is not possible to state categorically that women are more empathetic than men in all populations studied, despite the fact that authors have observed the opposite [8,[23][24][25][26][27].…”
Section: General Empathymentioning
confidence: 73%
“…Empathy is associated with the understanding that patients' experiences and feelings are mutually interacting factors in the development of an entity [7,8]. Measurements of empathy using different instruments have not been able to verify predictive validity; however, these measurements have a probative effect for the diagnosis of empathy in the formation of medical professionals [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Empathy is generally accepted as a desirable trait in medics and there are increasing calls to assess the level of empathy at some point during medical school, or prior to admission [10] [11] [12]. Indeed medically competence, socially responsible and emotionally empathetic, is some prominent attribute for incumbent entering the medical profession [2] [13] [14].…”
mentioning
confidence: 99%